Perencanaan dan Implementasi Inverter Satu Fasa Pada Pembangkit Listrik Tenaga Pikohidro di Air Terjun Watu Lumpang Mojokerto - Rhezal Agung; Naufal Ramadhani Akbar; Sapto Wibowo (Elposys: Jurnal Sistem Kelistrikan, 2022)
Renewable energy is a real source of energy that is easy and cheap to use, especially water, therefore it is often used for electrical energy generation systems by utilizing river or waterfall flows. One form of utilization is the Picohydro Power Plant (the smallestscale power plant). Where there is energy potential in an area but has not been utilized optimally, by utilizing the flow of waterfalls in Watu Lumpang Pacet Waterfall Tourism Mojokerto Regency using turbines as a drive and generator as a generator. However, because it is generated in the form of Direct Current (DC) electricity, it takes an inverter as a converter that can convert DC voltage to Alternating Current (AC). So it can be used to supply loads that mostly require AC electricity to operate.